An Error Analysis on Students’ Abstract of College Students at Banten Jaya University - Fajri, Dede (Journal of English Language Teaching and Literature (JELTL), 2021)
Writing is not a natural talent in language acquisition since it necessitates both editing and revising, making it appear to be a simple activity. A dictionary might be used by students to assist them use a foreign language in any situation. These exercises, however, may cause a number of mistakes in pupils’ writing tasks. In light of this, the purpose of this study is to detect students’ difficulties and grammatical mistakes during the academic writing process. In this study, mixed techniques were used to document the works of vocational college students and conduct interviews with them. The evidence on learners’ grammatical mistakes was gathered, transcribed, evaluated, and interpreted. The students’ mistakes were found to be in the following areas: tense (38.0%), preposition (11.7%), article (11.4%), conjunction (11.4%), omission (8.9%), subject-verb agreement (6.3%), and adverb (6.3%). (2.5 percent ). Meanwhile, according to the interview, most of the students (81.8 percent) utilized a translation tool such as Google translate to help with language competency during the writing process. Despite using a translation tool in writing, the majority of students (73%) said it was a challenging ability to master, and 18% considered the writing process was the most difficult of all language tasks.